SUBSTANSI KEBIJAKAN KURIKULUM BERBASIS LINGKUNGAN PADA SEKOLAH ADIWIYATA DI SMPN 2 KEBOMAS GRESIK - admin admin; Siti Nihlawati (Universitas Muhammadiyah Gresik, 2012)
One sucessful factor in the implementation of school Environmental Education (PLH) is the substance of the curriculum development policy. Research conducted in this Kebomas SMPN 2, using the observation, interviews, documents, and questionnaires, concluded that the substance of policy development in the school curriculum has a suitability or relevance in two ways, namely (1) the fit between the curriculum with the demands, requirements, conditions , and the development of society, and (2) conformity between the components of the curriculum, the contents in accordance with the objectives, the process according to the contents and goals, as well as the evaluation in accordance with the process, content and curriculum goals.